State building in Putin's Russia : policing and coercion after communism - Taylor, Brian D., 1964- (Cambridge University Press, 2011)
Showing that many of the weaknesses of the Russian state that existed under Boris Yeltsin persisted under Putin, this book argues that Vladimir Putin's strategy for rebuilding the Russian state was fundamentally flawed.